2018
DOI: 10.1007/978-3-319-95972-6_43
|View full text |Cite
|
Sign up to set email alerts
|

Toward Computing with Spider Webs: Computational Setup Realization

Abstract: Spiders are able to extract crucial information, such as the location prey, predators, mates, and even broken threads from propagating web vibrations. The complex structure of the web suggests that the morphology itself might provide computational support in form of a mechanical signal processing system -often referred to as morphological computation. We present preliminary results on identifying these computational aspects in naturally spun webs. A recently presented definition for physical computational syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Setting dir = 1 in the package express that the springs are tension-only elements. We have used a similar method to model a spider web with TMTDyn recently (Sadati and Williams, 2018). A drawback of such assumptions is that the model does not capture the crumbling of the fabric between the mesh nodes.…”
Section: Case Studies and Validationmentioning
confidence: 99%
“…Setting dir = 1 in the package express that the springs are tension-only elements. We have used a similar method to model a spider web with TMTDyn recently (Sadati and Williams, 2018). A drawback of such assumptions is that the model does not capture the crumbling of the fabric between the mesh nodes.…”
Section: Case Studies and Validationmentioning
confidence: 99%
“…This can be done by assuming the fabric as a net of equally distributed masses with connecting linear springs; a lumped-mass approximation of the fabric mesh. We have used a similar method to model a spider web with TMTDyn recently [30].…”
Section: A Pendulum With Fabric Sleeve Setupmentioning
confidence: 99%
“…This might also extend to their sensing properties. Previous works have explored the mechanical properties of spiderweb morphologies [ 15 ] while utilizing a variety of different fabrication and simulation methods [ 16 ]. Analysis of vibration signals showed that a web’s geometry and dynamics can improve the localization of prey through impact vibrations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of vibration signals showed that a web’s geometry and dynamics can improve the localization of prey through impact vibrations [ 10 ]. Furthermore, by 3D printing spiderwebs, their nonlinear properties have been highlighted, their dynamic effects have been explored [ 17 ], and their potential to act as a physical reservoir for computation has been proposed [ 15 ]. The development of soft sensors inspired by web structures has straddled a range of different fabrication and sensing modalities.…”
Section: Introductionmentioning
confidence: 99%